2009
DOI: 10.1111/j.1365-3016.2009.01091.x
|View full text |Cite
|
Sign up to set email alerts
|

Violent delinquency in a Brazilian birth cohort: the roles of breast feeding, early poverty and demographic factors

Abstract: Caicedo B, Gonçalves H, González DA, Victora CG. Violent delinquency in a Brazilian birth cohort: the roles of breast feeding, early poverty and demographic factors. Paediatric and Perinatal Epidemiology 2010; 24: 12–23.We investigated the association between breast feeding, economic factors and conviction for violent delinquency by age 25 years among subjects of the 1982 Birth Cohort from Pelotas, Southern Brazil. Information on breast-feeding pattern and duration was collected in childhood, during the 1983, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1
9

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 45 publications
(71 reference statements)
1
24
1
9
Order By: Relevance
“…[8][9][10][11][12][13] Our finding that a shorter duration of breastfeeding is associated with the child's attention problems is consistent with the results of Julvez et al 12 Our data also confirm the findings of previous studies that suggested the relationship between breastfeeding and child conduct problems or delinquency is due to the effect of confounding. 8,14 In addition, the present study is in agreement with the research of Fergusson and Woodward 9 that found no significant association between breastfeeding and offspring's anxiety and depression between 16 and 18 years. However, it contradicts a recent cohort study by Oddy et al 13 that found association between breastfeeding and adolescent internalizing problems at 14 years.…”
Section: Discussionsupporting
confidence: 93%
“…[8][9][10][11][12][13] Our finding that a shorter duration of breastfeeding is associated with the child's attention problems is consistent with the results of Julvez et al 12 Our data also confirm the findings of previous studies that suggested the relationship between breastfeeding and child conduct problems or delinquency is due to the effect of confounding. 8,14 In addition, the present study is in agreement with the research of Fergusson and Woodward 9 that found no significant association between breastfeeding and offspring's anxiety and depression between 16 and 18 years. However, it contradicts a recent cohort study by Oddy et al 13 that found association between breastfeeding and adolescent internalizing problems at 14 years.…”
Section: Discussionsupporting
confidence: 93%
“…The majority of the studies had a longitudinal design and started during pregnancy or right after birth: one was an intervention study 35 , one was retrospective 32 , and the others were prospective. Fourteen studies assessed only children 19 , 27 , 29 , 30 , 32 41 , three included only adolescents 28 , 31 , 42 , and one assessed both 26 .…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies assessed the association between breastfeeding and children's behavior 19 , 26 , 27 , 29 , 30 , 32 41 , and ten of them found some association between breastfeeding and child behavior 26 , 27 , 29 , 30 , 32 , 34 , 36 , 38 40 . Regarding breastfeeding assessment, seven studies assessed EBF 19 , 29 , 33 , 34 , 36 , 38 , 41 and twelve 26 , 27 , 30 , 32 35 , 37 41 studies assessed NEBF.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations